Coffee consumption as a double-edged sword for serum lipid profile: findings from NHANES 2005–2020 - Mo, Chaoyue; Duan, Xintong; Pu, Junlin; Zhou, Xuan; Zheng, Yongfeng; Wang, Shiyu (Frontiers in Nutrition, 2025)
BackgroundThere is growing interest in coffee's impact on cardiovascular health. As dyslipidemia is a major modifiable risk factor for cardiovascular disease and coffee may influence lipid metabolism, exploring the association between coffee consumption and serum lipid profile may provide further insights into coffee's cardiovascular effects and help inform dietary recommendations for patients with cardiovascular disease.Materials and methodsCross-sectional data were obtained from the National Health and Nutrition Examination Survey (NHANES) 2005–2020. The exposure variable was the daily coffee consumption, measured in cups, and the outcome variables were serum lipid profile components, including total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C). Weighted multiple linear regression, subgroup and interaction analyses, and restricted cubic spline (RCS) regression were used to evaluate the associations. Sensitivity analyses were conducted to assess the robustness of the results.ResultsEach additional cup of coffee consumed per day was associated with a 1.23 mg/dl increase in TC (95% CI: 0.68, 1.77) and a 1.22 mg/dl increase in LDL-C (95% CI: 0.77, 1.67). In the categorical analysis, among participants consuming ≥3 cups/day, each additional cup of coffee was linked to an increase of 8.45 mg/dl in TC (95% CI: 4.94, 11.96) and 7.86 mg/dl in LDL-C (95% CI: 5.01, 10.72), compared with non-drinkers. In females, HDL-C levels rose with coffee consumption up to 2.6 cups/day, after which they began to decline, showing an inverted U-shaped association. In males, a similar non-linear trend was observed for TG, with levels peaking at 3.0 cups/day before decreasing.ConclusionCoffee consumption exerts both beneficial and adverse effects on serum lipid profile. While it is positively associated with elevated TC and LDL-C levels, its relationships with HDL-C and TG are more complex and gender-specific. In females, HDL-C increased with intake up to 2.6 cups/day and declined thereafter, forming an inverted U-shaped pattern. In males, TG followed a similar trend, peaking at 3.0 cups/day. Although these changes were statistically significant, their clinical relevance may vary depending on individual cardiovascular risk profiles.